Restructuring Research: Communication Costs and the Democratization of University Innovation - Agrawal, Ajay; Goldfarb, Avi (American Economic Review, 2008)
We report evidence that Bitnet adoption facilitated increased research collaboration between US universities. However, not all institutions benefited equally. Using panel data from seven top engineering journals, Bitnet connection records, and institution ranking data, we find that middle-tier universities were the primary beneficiaries; they benefited largely by increasing their collaboration with top-tier schools. Furthermore, we find that the magnitude of this effect is greatest for co-located pairs. Thus, the advent of Bitnet – and likely of subsequent networks – seems to have increased the role of middle-tier universities as producers of new knowledge in the national innovation system. (JEL D85, I23, O31, O33)